Penerapan Kontrol Optimal Dalam Masalah Peminimumam Energi Yang Terbuang Pada Suatu Rangkaian Listrik - Endro Cahyono (Faculty of Mathtmatics and Natural Sciences, 2008)
The Optimal Control Problem frequently rise in rela program. In this article is analyzed the minimization of energy dissipated in a resistor component r (r = value of resistance) of electrical circuit which consist of one component r, one capasitor c (c = value of capasitance) which connected by current i(t) and voltage source v(t). If v(0) = v0 dan v(t1) = v1 then the control system models for the problem is v = ; with i(t) as a control. Performance functional for energy dissipated in the resistor r over the interval 0£t£t1 is ______________. In order energy dissipated in the resistor r minimum, so the control is i(t)=i0(t)=+(c/t1)(v1-v0)(constant). Then, if the circuit as an energy stored device and f v(0)=0 the it can be determinated. Efficiency rate (Ratio of the the energy stored over the energy delivered) in this circuit is